KEMANDIRIAN EKONOMI KAUM SARUNGAN: PENGEMBANGAN PENDIDIKAN ENTREPRENEUR DI PONDOK PESANTREN - Abdul Hamid; Zainal Kahfi (Al'Adalah, 2016)
Islamic boarding school is a traditional Islamic education where is used to study, understand, explore, appreciate and practice Islamic theory by stressing the importance of moral as a guide of daily activities. Basically, the purpose of the Islamic education is to teach the students in order to create independent people, except to God. It means that the education in the Islamic boarding school teaches the students to have an entrepreneur minded besides they have to dedicate their life to the God. The development of economy in Islamic boarding school has a big factor in promoting entrepreneurship. In Islamic boarding school area, the students are thought to be independent people and entrepreneur minded. Islamic boarding school tries to work independently without suspending their life to other people or to the private government. Institutionally, Islamic boarding school has given the real model by actualizing the spirit of independent through business by founding some units. In general, the development of the several businesses in Islamic boarding school is intended to consolidate the finance of Islamic boarding school, to train the students, and to empower economy.